MILITARY ART AND COMMANDERSHIP SKILLS OF AMIR TEMUR - Kholmonov Mansur Narzilloyevich (Journals Park Publishing, 2024)
The article provides information about the military art and skill of Amir Temur as a commander and various tactical actions in the deployment of a military army and methods of transferring a combatant army to khujum.
Keywords: mahurat, khujum, warrior army, military art, armor, amir ul-umaro, Military Council.